Multi-pronged approach to enhance education of children and adolescents with lupus, caregivers, and healthcare providers in New Jersey: Needs assessment, evaluation, and development of educational materials. (January 2021) - Hovde, Aldina M; McFarland, Cheryl AS; Garcia, G Melissa; Gallagher, Fran; Gewanter, Harry; Klein-Gitelman, Marisa; Moorthy, L Nandini
Background: Childhood Systemic Lupus Erythematosus (cSLE) patients are younger at diagnosis and have a more severe disease course compared to adult onset SLE patients and develop significant complications related to disease and or immunosuppression. Moreover, female and minority populations experience higher rates of cSLE, with African American, Afro-Caribbean, and Hispanic populations being at greatest risk and having poor prognosis Methods: The Pediatric Alliance for Lupus initiative addressed the dearth in education and resources in a multi-stage process. First, we conducted a need assessment identifying knowledge gaps among healthcare providers (HCPs), and resources needed to care for cSLE patients and their families. Second, we educated HCPs about the diagnosis and treatment of cSLE by Continuing Medical Education (CME) sessions/webinars (presented here). Third, HCPs participated in a Quality Improvement (QI) program on cSLE approved by the American Board of Pediatrics Maintenance of Certification Part 4. Finally, patients and caregivers were educated through the development of appropriate, culturally and linguistically sensitive cSLE resources. PAL disseminated materials among HCPs and the community to improve the awareness of the availability of these materials. Results: According to results from the statewide needs assessment (representative of every county throughout NJ), HCPs face significant challenges in providing care to cSLE patients and their families, in part due to the multi-systemic nature of the autoimmune disease. Conclusion: Based on this need, we developed educational sessions, with pre-post comparison data showing a significant increase in knowledge after HCP education. The 15 different materials developed as part of the endeavor is a major contribution to the cSLE community, HCPs and pediatric rheumatologists. Resources are available in multiple formats (PDF and web pages), and are accessible on the National Resource Center on Lupus, the latest web site of the Lupus Foundation of American that houses materials for SLE patients, their families, schools, HCPs, and the community at large. Improving cSLE knowledge will empower the children and adolescents and families by increasing their self-efficacy; and positively impact key health outcomes (transition readiness and HRQOL) that are not optimally addressed with current medical treatment alone.